As crenças facilitadoras e restritivas de familiares de paciente com HIV/AIDS que permeiam o tratamento - Sá, Camila Fioranelli de (Universidade Federal de São Carlos, 2022)
Introduction: When living with a relative with HIV/AIDS, the family demonstrates particularities and singularities in its functioning, which is permeated by a system of beliefs, which have great force on its members and on family functioning, having important healing and suffering in the family. General objective: To describe facilitating and restrictive beliefs about the treatment of adult patients with HIV/AIDS, from the perspective of family members who live with the problem. Methodology: Qualitative research with three family members, through semi-structured interviews in remote format, with thematic content analysis of data. Results: The beliefs of the family members in this study revealed that living with AIDS or being positive for the virus becomes normal when it involves maintaining the daily routine and quality of life, believing in the longevity of life in the face of therapeutic alternatives, having affective attitudes and caring not to contaminate the people around, demystify preconceptions and prejudices, which can be understood as beliefs that facilitate treatment and adherence. However, during the discovery of the diagnosis of the disease, negative and positive feelings and emotions permeated, which could be recognized as both restrictive and facilitating beliefs, depending on the family's behavior in the face of the discovery and the therapeutic process. Final considerations: Both restrictive and facilitating beliefs permeated the period of discovery of the diagnosis, but the family members sought to face and overcome such adversities, trying to break the restrictive beliefs, through religious and spiritual beliefs, valuing the treatment and promoting family cohesion.
The facilitating and restrictive beliefs of relatives of a patient with HIV/AIDS that permeate the treatment
Keywords: Síndrome de Imunodeficiência Adquirida; Crenças; Cultura; Família; HIV; Acquired Immunodeficiency Syndrome; Culture; Family; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PSIQUIATRICA